Islamic Studies Berbasis Research - Aji Damanhuri (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
The research aims to re-motivate research tradition in Islamic studies by developing the scientific and rational epistemological framework, acceptance of critiques, comprehensiveness, multidimensional, and applicative to solve universal humanity's problems. This research employs a descriptive philosophical method and interpretative analysis by portraying contemporary Islamic studies' reality and analyzing them using the already developed Islamic epistemological framework. It is expected that, from motivations written in this research, cosmopolitan Islamic civilization, which respects diversity, pluralism, human rights, women’s dignity, is ecologically sensitive, and is full of love with other people and other creatures of God, would emerge.